Role of Hydrogen Sulfide (H2S) in cell signaling and atherosclerosis : A review / Mohd Izani Othman - Othman, Mohd Izani (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2016)
Hydrogen sulfide (H2S) has been known for decades as a toxic gas. However, this gas has been discovered to be synthesised enzymatically in human tissues and is regarded as a novel gasotransmitter. H2S is a signaling molecule that involves and governs many biological functions of the body. It has been shown that H2S is associated with various disease conditions such as acute pancreatitis, sepsis, inflammation and atherosclerosis development. Current therapeutic approach may not benefit all patients with atherosclerosis. Therefore, the role of H2S as an anti-atherosclerotic agent has been the spotlight of cardiovascular medicine. Moreover, its implications in other diseases have also been studied extensively in order to develop new therapeutic approaches.